Pause (Mafsāl) Analysis Using Audio Praat Application in Shaikh Dr. Malik Husain Sya'ban's Lecture - Semaun Al Usman; Thonthowi; Tulus Musthofa (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2022)
Language is one of the important aspects of the key to understanding the specific goals and purposes used by people around the world, language as a tool serves as a significant communication tool developing in human civilization. this is evidenced by many types of supporting applications, the Praat program which can change sound waves that previously could only be heard now become visible to the human eye. In addition, the Praat program, is equipped with a device to see the tone motion, the magnitude of the pause, the length of the utterance, all of which are needed to determine the inaccuracy of an utterance or the error of the utterance. This study discusses the analysis of the lectures of Shaykh Dr.  Malik Husain Sya'ban based on the theory of mafsal pause in Ulumu al-lughohwiyah. The purpose and objective of this study is to determine the intonation of the pauses of these expressions. To answer these problems, in this study using qualitative descriptive analysis techniques in analyzing the results of observations made, then transcribed and then analyzed and data taken from the observations of researchers in the lectures of Shaykh Dr. Malik Husain Sya'ban.